Homosexual identity and network overlap predictors of HIV infection among older men from rural China: a case–control study - Yuan Li; Jia He; Yi Yang; Shuangfeng Fan; Jing Xi; ShiJiao He (BMJ Public Health)
Background The number of newly reported older (≥50 years old) people living with HIV/AIDS in China has been steadily increasing, and heterosexual transmission has been identified as the major route.Methods In this study, based on biopsychosocial model, a case–control study (74 cases vs 296 controls) was applied to find out predictors (21 potential ones) of HIV infection among older men from rural China. Binary logistic regression with backward selection was applied.Results Out of 21 potential predictors of HIV infection, 4 were confirmed: receiving HIV-related health education (HRHE) (OR 0.449, 95% CI 0.238 to 0.848), self-reported homosexual identity (16.517 (95% CI 1.073 to 254.182)), visiting female sex workers (FSW) (58.427 (95% CI 7.895 to 432.403)), complete non-overlap of intimate social network and sexual network (2.912 (95% CI 1.372 to 6.177)), partial overlap (3.334 (95% CI 1.536 to 7.236)).Discussion Findings from this study suggest current comprehensive prevention and control services need to be strengthened to provide effective HRHE including condom use to older men and help them to improve condom use, especially during visiting FSW and among self-reported homosexual older men. Moreover, increasing intimacy in their sexual relationships is necessary.